Demanda de dinero en América Latina, 1996-2016: una aplicación de cointegración en datos de panel (2018)
In this paper we consider a structural model of general equilibrium that allows us to deduce the demand for money as a function of the level of transactions and the opportunity cost of maintaining it. Through the application of the panel cointegration method and the FMOLS, we estimate the income and interest rate elasticities derived from a long-term relationship for a sample of 15 Latin American countries. The findings suggest the existence of a longterm equilibrium of money demand. The estimates for this exercise for the whole panel are consistent with the predictions of the theoretical model, but the magnitude of the elasticities differs when examined for each country. This seems to indicate that the money markets are not homogeneous and may be associated with different experiences in terms of macroeconomic performance.